2022
DOI: 10.1371/journal.pone.0276856
|View full text |Cite
|
Sign up to set email alerts
|

Is Ethiopian community-based health insurance affordable? Willingness to pay analysis among households in South Central, Ethiopia

Abstract: Background Community-based Health Insurance (CBHI) is a voluntary prepayment mechanism that guarantees the provision of basic healthcare services without financial barriers to underserved segments of the population in developing countries. The Government of Ethiopia launched the CBHI program to protect the community from high out-of-pocket health expenditure and improve health service utilization a decade ago. However, to improve the quality of healthcare services delivery in health facilities and cover the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Women who had a large number of living children were less likely to enroll in CBHI. In contrast, studies in revealed people with large family members were more likely to pay for the CBHI scheme than those with few family members (35,43). This could be attributed to the financial burdens that women with large family size had to enroll and renew their CBHI membership.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Women who had a large number of living children were less likely to enroll in CBHI. In contrast, studies in revealed people with large family members were more likely to pay for the CBHI scheme than those with few family members (35,43). This could be attributed to the financial burdens that women with large family size had to enroll and renew their CBHI membership.…”
Section: Discussionmentioning
confidence: 95%
“…However, this figure is by far higher than study findings in sub-Saharan African countries (8.5%) ( 18 ), Nigeria (less than 3%) ( 20 ), Ethiopia (4.7%) ( 15 ), Kenya (7.0%), and East African countries (7.56%) ( 19 ). Evidences in ethiopia revealed that CBHI enrolment depend on households’ willingness to pay, renew their CBHI membership, and enroll in the CBHI program, which highly dependent on the affordability of premium and availability of service ( 35 ). Besides, a strong government commitment is essential to achieve UHC.…”
Section: Discussionmentioning
confidence: 99%
“…Fee-for-service is the mechanism used to pay the provider ( 13 ). The Ethiopian government revised the CBHI plan premium from 240 Birr to 410 Birr per household per year since the prior contribution plus 25% government subsidies for all members were insufficient to meet the costs of healthcare services ( 14 ).…”
Section: Introductionmentioning
confidence: 99%